Effect of Maternal Age on Pregnancy or Neonatal Outcomes Among 4,958 Infertile Women Using a Freeze-All Strategy - Lin, Jiaying; Huang, Jialyu; Zhu, Qianqian; Kuang, Yanping; Cai, Renfei; Wang, Yun (Frontiers in Medicine, 2020)
The freeze-all strategy has been increasingly employed in the context of in vitro fertilization (IVF) cycles globally, but the relative advantages of this approach are not entirely understood. Herein we sought to assess how maternal age affected pregnancy and neonatal outcomes in women who had undergone frozen–thawed embryo transfer (FET). In this retrospective analysis, we assessed outcomes for 4958 total women at the University-affiliated Tertiary Centre from January - December 2017. We compared pregnancy and neonatal outcomes between a control group (< 30 years old) and groups of more advanced maternal age (30-34, 35-37, 38-40, 41-43, and 44–50 years). We found that live birth rates (LBR) for the first FET cycle following a freeze-all strategy significantly declined with increasing maternal age, with the most pronounced declines in the 35-37 and 38-40 age groups (LBR: 51.12% at <30 years, 43.86% at 30-34 years, 41.64% at 35-37 years, 25.67% at 38–40 years, 15.58% at 40–43 years, and 4.78% at 44–50 years, respectively). Rates of preterm delivery (PTD), very PTD, low birth weight (LBW), very LBW, term LBW, preterm LBW, and macrosomia were comparable across study groups. Together these results thus suggest that increasing maternal age has an adverse impact on pregnancy outcomes without affecting PTD or LBW risk in the context of a freeze-all strategy.